Amanaedu: uma nuvem computacional para apoiar o ensino técnico e profissionalizante no estado do Pará - GÓES, Anderson Silva de Oliveira (Universidade Federal do Pará, 2017)
This paper presents a cloud computing structure called AMANAEDU. It was developed to help solving some of the serious problems of the public technical and professional education in the state of Para. Many of these problems involve adverse factors related to geographical and social issues. An analysis of the national context shows the growth in the use of educational computing in this type of education, evidenced by good results obtained in digital inclusion programs run by states governments, which are increasingly being linked to distance education initiatives. In Para, the main program in this model is called NavegaPará, which had its infrastructure utilized in the execution of the object of this research. The development of the components of this cloud was based on theoretical and methodological models widely accepted by the academic community, such as Constructivism and Instructionism. The best programming practices for cloud computing were used in this study. The application layer includes three portals used for distance and semi – presential professional education: SEUTED for centralized access to all Virtual Learning Environments (VLE) available in the cloud, PROTVEDU, which uses multimedia streaming for the transmission of audio and video related to education and PROA, a portal used as storage repository for learning objects. Together, these elements can serve as the basis for a new educational approach that can be implemented at all levels of technical and professional education.